Clinical characteristics, mid-term outcomes and management of asymptomatic primary hyperparathyroidism: A multicentre retrospective cohort study - Engin, Ismail; Tuna, Mazhar Muesluem; Koroglu, Ekin Yigit; Cakir, Bekir; Firat, Sevde Nur; Yagci, Hueseyin; Sahin, Mustafa (Springer, 2025)
Purpose The primary objective of this study was to retrospectively evaluate the demographic, biochemical, and clinical characteristics of patients with asymptomatic primary hyperparathyroidism (aPHPT), analyze their long-term outcomes, and discuss the effectiveness of current therapeutic strategies in light of the existing literature. We anticipate that our study will provide clinicians with guidance regarding surgical decision-making beyond the standard criteria for aPHPT. Methods This was a nationwide, multicenter, observational, retrospective cohort study. All tertiary care endocrinology departments across the country were invited to participate. Center inclusion criteria required the enrollment of a sufficient number of aPHPT patients, confirmed by careful diagnostic evaluation in accordance with established guidelines, regular follow-up for at least one year, and systematic monitoring for complications. Results Data from 27 centers representing various regions of Turkey were included in the study. A total of 829 patient records were reviewed, and after excluding 25 patients who did not meet eligibility criteria, 804 patients were included in the final analysis. The mean age was 55.59 +/- 11.54 years, with a female predominance (85%, n = 683). The baseline prevalence of comorbidities was as follows: hypertension in 43% (n = 346), diabetes mellitus in 27.1% (n = 216), and cardiovascular disease in 10.8% (n = 87) of patients. Bone mineral density (BMD) measurements were available for 701 patients, among whom osteoporosis was present at 23.4% and osteopenia at 50.5%. Glomerular filtration rate (GFR) significantly declined by the third year compared to baseline (p = 0.003). The prevalence of cardiovascular disease significantly increased at year three compared to baseline and the first year (p = 0.002). A significant association was found between the presence of osteoporosis and lower baseline serum magnesium levels (p < 0.001), particularly among patients with magnesium levels below 1.6 mg/dL compared to those with levels within the normal range (1.6-2.5 mg/dL). Additionally, patients with osteoporosis demonstrated significantly lower serum phosphate levels compared to other groups (p < 0.001). Conclusion The management of asymptomatic PHPT continues to present numerous unanswered questions. Hypertension, cardiovascular disease, and diabetes mellitus were found to be more prevalent among aPHPT patients compared to the general population. The observed increase in cardiovascular events over time suggests that cardiovascular disease could become a more prominent factor in future surgical decision-making. Furthermore, the significant decline in GFR over follow-up may necessitate revisiting the surgical threshold of GFR < 60 mL/min in future guidelines. Routine assessment of serum magnesium and phosphate levels should be considered, particularly in patients at high risk for osteoporosis. Future research may further redefine surgical indications in the management of aPHPT.
Keywords: Bone-Mineral Density